Riverine litter assessment and recycling potential along Sungai Kelantan at Kampung Pasir Era, Kelantan, Malaysia - Syed Alwi, Syarifah Nur Najwa; Abd Manaf, Latifah; Amiruddin, Abd Muhaimim; Kpalo, Sunday Yusuf; Nazibudin, Nazatul Akmal (Malaysian Institute Of Planners, 2023)
Nowadays in Malaysia, riverine litter has become a major environmental problem. Knowledge of solid waste generation, composition and recyclability is necessary for accurate decision making in the management strategy of municipal solid waste. This study is conducted to assess riverine litter and its recycling potential along Sungai Kelantan at Kampung Pasir Era Kelantan. The objectives are to determine the generation and composition of riverine litter and to evaluate the recycling potential of the litter. The waste samples are collected over a 14- day period at three different zones within the study area. Through quantification method, composition, proportion and the average daily total weight of the litter were determined. Findings show that the total weight of waste collected for all zones throughout the 14 days operation was found to be 70.912 kg out of which the upper-bank generated 25.9 kg. The result also shows that plastic has the highest contribution to riverine litter with 68.20. Additionally, estimated revenue from potentially recyclable litter generated in 14 days was RM33.96. This study provides the local authority and relevant agencies with baseline information for effective management of riverine litter based on recycling potentials.